Relationship of Circulating Endothelial Cells, Endothelial Progenitor Cells, and Endothelial Dysfunction after High-Intensity Exercise: Role of Nitric Oxide - Kinanti, Rias Gesang; Sargowo, Djanggan; Widjajanto, Edi; Rifa’i, Muhaimin (The Journal of Experimental Life Science, 2023)
Endothelial dysfunction after high-intensity exercise occurs through various mechanisms characterized by decreased nitric oxide (NO) bioavailability. This study aims to determine the relationship between circulating endothelial cells (CEC), endothelial progenitor cells (EPC), and endothelial dysfunction after high-intensity exercise through an experiment using male Wistar strain rats. This study uses the randomized control group posttest-only design. A total of 32 male Wistar rats aged 20-22 weeks with a body weight of 140±20 g were taken randomly and divided into two groups. Group 1 (n=16), the control group, was given low-intensity exercise. Meanwhile, group 2 (n=16), named the treatment group, was given high-intensity exercise. The groups were run on a special treadmill where light-intensity exercise is done at a speed of 5-8 meters.minute-1 for 30 minutes and high intensity at 25-30 meters.minute-1 for 30 minutes. The treatment was performed at 5 to 10 pm, 3 times weekly for 12 weeks. Blood and aortic tissue samples were taken after the mice were rested for 12 hours after the last exercise. ELISA and Flow cytometry measured NO, CEC, and EPC levels. This research showed that CEC and EPC expression and high-intensity exercise have a positive relationship, yet not significant to the occurrence of endothelial dysfunction (NO), with a value of Sig. (0.111); p > 0.05, and the relationship value is r = 0.414 (R²= 17.15%). In conclusion, endothelial dysfunction after high-intensity exercise is not associated with CEC and EPC expression, which indicates endothelial damage.  Keywords: exercise, circulating endothelial cells, endothelial dysfunction, endothelial progenitor cells, nitric oxide